Spirituality, loneliness and mental health in Blackfeet American Indian adults. - Betty Henderson-Matthews; Reece Kothe; Skye Gilham; Zachary J Wood; George Heavy Runner; Lester Johnson Iii; Mary Ellen Lafromboise; Melveena Malatare; Emily Salois; Neha A John-Henderson (PLoS ONE)
Prior work documents a relationship between spirituality and mental health in American Indians. Separately, a robust literature links loneliness to indices of mental health. The current study is grounded in Community Based Participatory Research methods and investigates the relationship between spirituality, loneliness and indices of mental health. In a sample of 276 Blackfeet American Indian adults, a linear regression controlling for age, gender, education and marital status showed that higher levels of spirituality predicted lower levels of loneliness (β = -.31, t(266)=-5.34, p < .001, r2 change = .10). and lower levels of symptoms of depression= (β = -.24, t(267)=-4.02, p < .001, r2 change = .06) and anxiety (β = -.33, t(267)=-5.94, p < .001, r2 change = .11). Further analyses showed that higher levels of spirituality were linked to fewer symptoms of depression in part through lower levels of loneliness indirect effect (standard error, SE)= -.42 (.11), 95% CI= [-.65,-.23]. Similarly, higher levels of spirituality were linked to fewer symptoms of anxiety in part through lower levels of loneliness (indirect effect (SE)=-.46 (.12), 95% CI= [=-.70, -.26]. The findings offer preliminary evidence to support the notion that spirituality may confer benefits for mental health in part by decreasing loneliness for Blackfeet American Indian adults. Future work should investigate the social and behavioral pathways through which spirituality is linked to loneliness and mental health in this community.